The Role of Accounting to Increase Awareness of SME in Paying Zakat - gustiningsih, Diah ayu; Asirie, Ronny Ahmad Al (SENTRALISASI, 2024)
This research aims to see the role of accounting in increasing awareness of SME households in paying zakat. This study used descriptive qualitative method. Data collection was carried out through interviews. The research results show that accounting is used to make it easier for SMEs to explain whether their wealth has reached the nisab and haul. This information can be seen from the notes for current assets and current liabilities in the business financial statements. In addition, it was found that good understanding or literacy of zakat can suppress opportunistic behavior, so that SMEs' awareness of paying zakat can increase, especially when SMEs have information to determine whether their SMEs have reached the nisab or haul.